2017
DOI: 10.1177/1010428317695932
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of sorting nexin 10 is associated with overexpression of miR-30d during liver cancer progression in rats

Abstract: As of 2012, liver cancer was the second leading cause of death worldwide, and hepatocellular carcinoma is the most common primary cancer of the liver. The identification of molecules that might be molecular markers or therapeutic targets is urgently needed to improve clinical management. Based on a microarray analysis performed in our laboratory, we selected six genes-namely, ANXA2, DYNLT1, PFKP, PLA2G7, KRT19, and SNX10-as candidates for validation as tumor markers of liver cancer in a rat model. Their patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Supporting our patient data, a recent report showed that miR‐30d expression was high in hypoxic CRC cell lines and in primary tumours from patients who failed adjuvant therapy (presumably by metastatic progression, but not specified [33]). In hepatocellular carcinoma, miR‐30d was shown to be highly expressed [49–51] and promote intrahepatic tumour cell invasion and implant tumours [49]. Interestingly, the great majority of the metastatic cases in the present study had dissemination to the liver, suggesting that circulating exosomal miR‐30d‐5p from their primary tumours may have contributed to this organ‐specificity of metastasis [52].…”
Section: Discussionmentioning
confidence: 86%
“…Supporting our patient data, a recent report showed that miR‐30d expression was high in hypoxic CRC cell lines and in primary tumours from patients who failed adjuvant therapy (presumably by metastatic progression, but not specified [33]). In hepatocellular carcinoma, miR‐30d was shown to be highly expressed [49–51] and promote intrahepatic tumour cell invasion and implant tumours [49]. Interestingly, the great majority of the metastatic cases in the present study had dissemination to the liver, suggesting that circulating exosomal miR‐30d‐5p from their primary tumours may have contributed to this organ‐specificity of metastasis [52].…”
Section: Discussionmentioning
confidence: 86%
“…SNX10 is believed to be a regulator of macrophage polarization ( 67 ). SNX10 has also been shown to have potential role in liver cancer by suppressing microRNA-30d ( 68 ). CCBP2 and GAS7 are two other genes inhibited by U-STAT1.…”
Section: Discussionmentioning
confidence: 99%
“…Sorting nexin 10 (SNX10), a protein maintaining endosome/lysosome homeostasis a tumor, can suppress the tumorigenesis and progression of colorectal cancer, liver cancer and stomach cancer (51,52). Cervantes-Anaya N et al demonstrated SNX10/V-ATPase pathway regulated ciliogenesis in vitro and in vivo (52). Prostaglandin D synthase (PTGDS), which catalyzes the conversion of prostaglandin H2 into prostaglandin D2 (PGD2), has been intensely studied (53).…”
Section: Discussionmentioning
confidence: 99%